Regulates The Death Penalty Perspective From The Purpose Of Punishment As Stipulated In The Indonesian Penal Code (KUHP) - Lufsiana; Setiawan Negara, Dharma; Nainggolan, Samuel Dharma Putra; Sinambela, Jamalum (Jurnal Independent, 2024)
Abstract The death penalty is the most severe type of punishment imposed on a defendant. The death penalty regulations in the New Criminal Code are different from the Criminal Code which is currently still in force. This research is normative legal research using a statutory approach and a conceptual approach regarding the Death Penalty and the Purpose of Punishment itself. This research aims to analyze the death penalty regulations in the New Criminal Code which are different from the Criminal Code which is currently still in force.